Relevância do assited hatching com laser em um programa de ovo-doação utilizando banco de óvulos criopreservados: Um estudo prospectivo randomizado - Braga, Daniela Paes de Almeida Ferreira; Figueira, Rita de Cássia Savio; Setti, Amanda Souza; Colturato, Simone Santaguita; Iaconelli Jr., Assumpto; Borges Jr., Edson [UNESP] (Elsevier, 2011)
Objective: This prospective randomized trial evaluated if there is an improvement in clinical outcomes when assisted hatching is performed in embryos derived from vitrified oocytes in an ovum donation program. Methods: Sixty oocyte recipients undergoing donation program using egg-cryobanking were randomly allocated to the assisted hatched (AH, n=30) or control group (n=30). Pregnancy and implantation rates were compared between the groups. Vitrification and warming procedure were carried out according to the Cryotopmethod. Immediately before embryo transfer, embryos undergoing laser-assisted hatching had the zona pellucida thinned using a 1.48 μm wavelength diode laser. Results: A total of 288 vitrified MII oocytes were warmed for the 60 recipients (4.8 oocytes per recipient). Out of 288 vitrified oocytes, 273 (94.8%) survived. All surviving oocytes were sperm injected and 228 displayed 2 pronucleus 16-18h after injection (83.5%). There were 172 good quality embryos transferred. Twenty four patients achieved clinical pregnancy (total pregnancy rate of 40%). The clinical pregnancy rate did not differ between AH and control groups (44.4% and 33.3%, respectively, p=0.1967), however AH resulted in a significant higher implantation rate (31.6% and 18.4%, p=0.0206). These findings were confirmed by the regression models either for pregnancy (OR = 1.14; IC 95% = 0.80-.72; p= 0.766), as for the implantation rate (RC:19.45, P=0.041). Conclusions: Our evidences demonstrated the effectiveness of the AH in embryos derived from warmed oocytes and suggest that oocyte cryopreservation is a valuable tool to provide successful outcomes in an egg donor program. © Todos os direitos reservados a SBRA - Sociedade Brasileira de Reprodução Assistida.
Relevance of laser-assisted hatching in an oocyte donation program using egg-cryobanking: A prospective randomized study
Keywords: Assisted hatching; Egg donation program; Egg-cryobanking; Oocyte vitrification; controlled study; cryobanking; cryotherapy; diode laser; embryo; embryo transfer; female; human; infertility therapy; laser assisted hatching; major clinical study; nidation; oocyte donation; oocyte survival; pregnancy; prospective study; qualitative analysis; survival; treatment outcome; vitrification; zona pellucida